Effects of Citrus limon Extract on Oxidative Stress-Induced Nitric Oxide Generation and Bovine Teeth Bleaching - Soon-Jeong Jeong (The Korean Society of Dental Hygiene Science, 2021)
Background: We aimed to investigate the effect of Citrous limon extract (CLE) on oxidative stress-induced cytotoxicity and nitric oxide (NO) generation and the tooth bleaching effect of CLE as a substitute for hydrogen peroxide (H2O2) and determine the feasibility and application of CLE as a safe and effective natural tooth bleaching agent. Methods: The protective effect of CLE on H2O2-induced cytotoxicity in Raw264.7 macrophages was investigated by the MTT assay. The inhibitory effect of CLE on the generation of H2O2-induced NO was confirmed by the NO assay, and the changes in inducible nitric oxide synthase (iNOS) protein expression were confirmed by western blotting. Stained bovine teeth were treated with/without 15% and/or 35% CLE and H2O2, 15% sodium bicarbonate (NaHCO3) for 3 hours, and were irradiated with/without bleaching light (BL) for 15 minutes. The color change of the treated bovine tooth surface was measured using a colorimeter. Results: The viability of Raw264.7 cells treated with each concentration of CLE and 500 μM H2O2 significantly increased as CLE increased, and NO generation and iNOS protein expression were significantly reduced in cells treated with 300 μg CLE+/500 μM H2O2+ and 300 μg CLE+/500 μM H2O2+/150 μg NaHCO3+. The bleaching effect of 35% CLE+ was higher than that of 15% CLE+ and 15% NaHCO3+, and the effect was similar to that of 15% H2O2+. The 35% CLE+/15% NaHCO3+ showed the greatest bleaching effect and was higher than that of the groups irradiated with the BL. The greatest bleaching effect was observed with 35% CLE+/15% NaHCO3+, followed by 35% H2O2+/BL+. Conclusion: CLE inhibited oxidative stress-induced cytotoxicity and NO generation in Raw264.7 cells and, could replace H2O2, which causes side effects and risks in teeth breaching treatment. It showed greatest teeth bleaching effect when combined with NaHCO3. CLE is an effective and safe natural tooth bleaching substitute.